CT-guided hook-wire localisation prior to video-assisted thoracoscopic surgery of pulmonary lesions. Issue 10 (October 2017) - Gruber-Rouh, T.; Naguib, N.N.N.; Beeres, M.; Kleine, P.; Vogl, T.J.; Jacobi, V.; Alsubhi, M.; Nour-Eldin, N.A.
Abstract : Aim: To assess the feasibility, safety, and efficacy of computed tomography (CT)-guided pulmonary nodule localisation using a hooked guide wire before video-assisted thoracoscopic surgery (VATS). Materials and methods: The study included 79 patients with a history of malignancies outside the lung associated with pulmonary nodules. Mean lesion size was 0.7 cm (range 0.5–1.8 cm) and the mean lesion distance to the pleural surface was 1.5 cm (range 0.2–5 cm). All lesions ( n= 82) were marked with a 22-G hook wire. The technique was designed to insert the tip of the hook wire within or maximally 1 cm from the edge of the lesion. The Mann–Whitney U -test was used for univariate analyses and Fisher's exact test for categorical values. Results: The hooked guide wire was positioned successfully in all 82 pulmonary nodules within mean time of 9 minutes (8–20 minutes, SD: 2.5 minutes). The procedure time was inversely proportional to the size of the lesion (Spearman correlation factor 0.7). Minimal pneumothoraces were observed in five patients (7.6%). Pneumothorax was not correlated to the histopathology of the pulmonary nodules ( p> 0.09). Focal perilesional pulmonary haemorrhage developed in four patients (5%). Both haemorrhage and pneumothorax were significantly correlated to lesions <10 mm ( p= 0.02 and 0.01 respectively). The volume of resected lung tissue was significantly correlated to lesions of increased distance from the pleural surface ≥2.5 cm in comparison to lesions of <2.5 cm from the pleural surface. Conclusion: CT-guided pulmonary nodule localisation prior to VATS could enable safe, accurate surgical guidance for the localisation of small pulmonary nodules. Highlights: Positioning the hook guide-wire inside the lesion could significantly minimise the volume of resected lung tissue. The volume of resected lung tissue was greater for lesions >2.5 cm from the pleural surface compared to lesions <2.5 cm from the pleural surface. The overall incidence of pneumothorax associated with this technique was (7.6%) and the risk was greater in patients with emphysema. Haemorrhage and pneumothorax were more likely in lesions <10 mm in diameter.